Periplaneta americana extract alleviates steatohepatitis in a mouse model by modulating HMGB1-mediated inflammatory response - Xiao, Yang; Gao, Chongqing; Wu, Junru; Li, Jing; Wang, Lijuan; You, Yang; Peng, Tianqi; Zhang, Keke; Cao, Mingrong; Hong, Jian (Frontiers in Pharmacology, 2022)
Alcoholic abuse and obesity are the most common lifestyle implications of chronic liver injury, and always act synergistically to increase the risk of mortality. Periplaneta americana has a long history of being applied in medicine, including wound healing, antitumor, antibacterial, antiviral, antifibrotic, and cardiomyocyte-protecting. Ganlong capsule (GLC), a natural prescription drug extracted from Periplaneta americana, has been widely used in HBV-related symptoms. However, the anti-steatohepatitis efficacy and mechanisms of GLC have not yet been characterized. Here, we found the protective effect of GLC on the development of hepatic steatosis, oxidative stress, and inflammation in vivo under alcohol exposure combined with a high-fat and high-cholesterol diet (HFHC). Consistently, GLC exhibited a hepatoprotective property by preventing hepatocytes from oxidative stress injury and lipid accumulation in vitro. In addition, it exerted an anti-inflammation characteristic by reducing macrophage recruitment and decreasing the expression of pro-inflammatory genes in vivo and in vitro. Mechanically, GLC serum, isolated from GLC-treated mice, reduced extracellular high-mobility group box 1 (HMGB1) of dying hepatocytes; and suppressed subsequent M1 polarization of macrophages in the co-culture system. Furthermore, GLC serum inhibited inflammatory response via suppressing the HMGB1 release and blocking the downstream TLR4/NF-kB pathway. Collectively, GLC alleviates steatohepatitis induced by alcohol consumption and obesity through inhibition of the HMGB1-mediated inflammatory cascade. GLC might be a therapeutic candidate for the treatment of steatohepatitis developed by alcohol abuse and metabolic disorders.